Fishery discards and incidental mortality of seabirds attending coastal shrimp trawlers at Isla Escondida, Patagonia, Argentina - Marinao, Cristian Javier; Yorio, Pablo Martin (The Wilson Journal of Ornithology)
We evaluated seabird attendance and incidental mortality at coastal trawl vessels targeting Argentine red shrimp (Pleoticus muelleri) in the Isla Escondida fishing area, Argentina, during 2006-2007 and 2007-2008. Eight seabird species attended vessels, and the most frequent and abundant seabird (percent occurrence, mean number per haul) in the two seasons was the Kelp Gull (Larus dominicanus) (100%, 112.3 and 100%, 263.4, respectively), followed by the Black-browed Albatross (Thalassarche melanophris) (85%, 17.6, and 90%, 32.4, respectively). Eleven Magellanic Penguins (Spheniscus magellanicus) and one Imperial Shag (Leucocarbo atriceps) were killed in nets with a mean capture rate of 0.003 and 0.0003 birds per haul, respectively. The estimated total number of birds killed was 53 penguins and five shags considering the total number of hauls made by the fishery in the two seasons. No contacts between seabirds and warp cables were recorded. Coastal shrimp vessels generally operated between 15 and 20 km offshore, at a mean distance from the main Kelp Gull colony (Punta Tombo) of 43.9 km. At least 100 fish and invertebrate species were discarded, mostly Argentine hake (Merluccius hubbsi). Total amount discarded per season by this coastal fishery in the two seasons was estimated at 3,284 and 6,590 tonnes, respectively. The coastal shrimp fishery in the Isla Escondida area appears to have a small impact on seabirds in terms of incidental mortality but provides significant amounts of supplementary food during the breeding season of the Kelp Gull. Fil: Marinao, Cristian Javier. Universidad Nacional de la Patagonia "San Juan Bosco". Facultad de Ciencias Naturales - Sede Trelew; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Yorio, Pablo Martin. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina. Wildlife Conservation Society; Estados Unidos